Moringa oleifera: a new hope on breast cancer treatment / Muhammad Syahmi Mohd Zaid and Ts Faikah Awang @ Ismail - Mohd Zaid, Muhammad Syahmi; Awang@ Ismail, Faikah (Universiti Teknologi MARA, Negeri Sembilan, 2023)
Moringa oleifera is a species that comes from the kingdom Plantae, division Magnoliophyta, class Magnoliopsida, order Brassicales, family Moringaceae, genus Moringa. Moringa oleifera are known to go by many names such as Horseradish tree, Benzolive, Drumstick tree, “Sajna”, “Kelor”, “Saijihan”, and “Marango”. The name of the plant was bestowed by botanist Carl Linnaeus with the scientific name “Moringa oleifera.” The plant’s genus name “Moringa” originates from the Tamil word “murungai” and the Malayalam word “muringa,” both of which pertain to the plant. The species name “oleifera” is derived from the Latin word “oleum,” signifying oil, and alludes to the plant's seeds that are abundant in oil. Moringa oleifera is known by several other names, including drumstick tree, horseradish tree, ben oil tree, and miracle tree. Moringa oleifera also known to the locals in Malaysia as “pokok kelor.”